2010
DOI: 10.3390/molecules15042520
|View full text |Cite
|
Sign up to set email alerts
|

An Expeditious Synthesis of N-substituted Pyrroles via Microwave-Induced Iodine-Catalyzed Reactions under Solventless Conditions

Abstract: An expeditious synthesis of N-substituted pyrroles has been developed by reacting 2,5-dimethoxy tetrahydrofuran and several amines using a microwave-induced molecular iodine-catalyzed reaction under solventless conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…Several heterocyclic compounds (both synthetic and natural) are widely known and many of them possess significant biological activities [1][2][3][4][5]. In 2013, four out of top six and nine out of top twenty one highest selling drugs were small molecule heterocyclic compounds [6].…”
Section: Introductionmentioning
confidence: 99%
“…Several heterocyclic compounds (both synthetic and natural) are widely known and many of them possess significant biological activities [1][2][3][4][5]. In 2013, four out of top six and nine out of top twenty one highest selling drugs were small molecule heterocyclic compounds [6].…”
Section: Introductionmentioning
confidence: 99%
“…The formation of the N-substituted pyrroles in high yields (∼94%) may be explained by the formation of an azomethine ylide via decarboxylation and a subsequent 1,5-proton shift to give the more stable zwitterions, which can be easily transformed to the more stable product to gain aromatic character [4]. Banik and co-workers demonstrated that a solvent-free mixture of 2,5-dimethoxytetrahydrofuran and an amine with iodine (5 mol%) in an automated microwave oven afforded in short reaction time (∼5 min) N-substituted pyrroles in good yields (75-98%) [5]. A microwave process is highly beneficial in a small-scale parallel synthesis of 2-aminothiophenes by the Gewald reaction [6].…”
Section: 23 Five-membered Heterocycles With N and S Atoms: Synthesimentioning
confidence: 99%
“…A catalytic enantioselective synthesis of 4-substituted-4,5-dihydro-1H- [1,5]benzodiazepin-2(3H)-ones employing an efficient hydrogenation protocol was developed by Rueping et al [142]. The target products were obtained in good yields (69-95%) with excellent enantioselectivities (83-99% ee) and broad functional group tolerance.…”
Section: Seven Membered Heterocycles With Two Heteroatoms: Microwave-mentioning
confidence: 99%
See 1 more Smart Citation
“…Pyrrole derivatives have also been reported as antimicrobial and antioxidant [15,16], anti-HIV [17], anticancer [18,19], antagonists of 5-HT7 receptor [20], antihepatitis [21], and as antifungal agents [22] as well as cognition enhancers [23] Banik et al [24] reported an expeditious synthesis of N-substituted pyrroles 1 by reacting 2,5-dimethoxy tetrahydrofuran and several amines under microwave irradiation using iodine as a catalyst. 2-Azetidinones and pyrroles are two highly important classes of molecules in organic and medicinal chemistry.…”
Section: Pyrrolesmentioning
confidence: 99%